PENGARUH BIAYA LINGKUNGAN DAN GREEN ACCOUNTING TERHADAP KINERJA KEUANGAN DENGAN SIZE DAN LEVERAGE SEBAGAI VARIABEL KONTROL - Nida Dini Rofi'ah (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2024)
This study aims to the test and analyse the effect of environmental cost and green accounting on financial performance with size and leverage as a control variabels. This population in this study were 83 energy sector companies listed on IDX (Indonesian Stock Exchange) in 2020 – 2022. Sample were taken using purpose sampling method with data analysis techniques using linear regression analysis. Data analysis was carried out using the statistical application called SPSS. Based on the results of the study, it can be seen that partially environmental cost and green accounting has effect on financial performance. While silmutaneously environmental cost and green accounting has effect on financial performance using size and leverage as a control variabels